The geographical distribution of fish, benthic coverage and sea urchins in the coastal zone of Lesvos island - Tsalkatis, Panagiotis (2022)
It is known that the last decades, global warming, overfishing and pollution are the main reasons for fish population declines, degradation of habitats and increase of barrens on shallow rocky reefs. Here, we investigated the levels of fish species richness, the benthic coverage categories and the sea urchin abundance along the coastline of the island Lesvos. For this purpose, 32 sampling sites were chosen randomly through the coastline with minimum distance 5.4 and maximum 20 km. In 21 sites we had mobile and in 11 hard substrate. Also, we categorized the sampling sites according to their geographical location. We found that between benthic coverage categories there is a small statistical difference between the east side of the island and the gulfs. The fish distributions for abundance have shown also some differences between different geographical areas. Finally, the sea urchin abundance did not appear to correlate with benthic categories.